EXAMINING KEY DRIVERS FOR ONLINE IMPULSE BUYING IN MALAYSIAN’S PUBLIC UNIVERSITIES STUDENTS - Man Hong Lu; Muhammad Azim Abu Hassan Sha’ari; Jia Jin Chee; Jie Hunn Chen; Shwu Ching Bong (Jurnal Manajemen dan Kewirausahaan, 2021)
With the current growth of the internet, there are signs of e-commerce in Malaysia growing and booming, such as Lazada, Mudah.my, Shopee, and others. Malaysians have been increasingly reliant on the internet to obtain product details and to make purchases. This motivates e-commerce entrepreneurs to devise a new strategy for increasing sales by increasing the rate of online impulse purchases among visitors to online shopping platforms. The aim of this research is to look into the connection between key-driven and online impulse buying. The aim of this research is to create a framework that represents the main drivers of online impulse buying among Malaysian public universities. The study also addresses empirical results from a 303-respondent online survey conducted with SPSS version 22.0 and Smart-PLS version 3.0. The research paradigm is focused on the Theory of Planned Behaviour (TPB) Model, which includes online impulse buying as a dependent variable and three independent variables (Flow Experience, Perceived Usefulness, and Trust). Non-probability methods, judgement sampling, and convenience sampling were used to select respondents in this research, who ranged in age from 19 to over 30 years old and were university students in Malaysia. In addition, this research paves the way for future studies by identifying relevant online purchase platform providers and product categories to conduct a new study.